2019
DOI: 10.35965/jbm.v1i2.294
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Return on Asset Dan Tobin’s Q Terhadap Volume Perdagangan Saham Pada Perusahaan Perbankan Yang Listing Di Bursa Efek Indonesia Periode Tahun 2013-2017

Abstract: The ability of company to earn profit in its operational activities as a main focus in evaluation of banking performance, because from the company's profits it will be known the ability of company to fulfill its obligations to investors as well, which is an important element in creating corporate value that shows its prospects in the future. The objective of research was: (1) to analyze and explains the influence of ROA on the volume of stock trading of banking companies listed on the IDX for the period 2013-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Table 6 shows Tobin's Q ratio does not affect the market reaction. The results of this study are not in line with research conducted by Reny et al (2019); Saputra (2018);and Timothy &;Hutabarat (2022) who stated that tobin's Q ratio has a positive and significant effect on trading volume activity (TVA). This study assumes that investors do not know the value of Tobin's Q ratio, which describes the company's investment growth potential.…”
Section: Discussioncontrasting
confidence: 99%
“…Table 6 shows Tobin's Q ratio does not affect the market reaction. The results of this study are not in line with research conducted by Reny et al (2019); Saputra (2018);and Timothy &;Hutabarat (2022) who stated that tobin's Q ratio has a positive and significant effect on trading volume activity (TVA). This study assumes that investors do not know the value of Tobin's Q ratio, which describes the company's investment growth potential.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have found a positive and significant effect of profitability on trading volume. Some of them are by Reny, et al (2019) discovering that partially Return on Assets (ROA) and Tobin's Q had a positive and significant effect on stock trading volume, and Return on Assets (ROA) and Tobin's Q had a simultaneous positive and significant effect on the trading volume of shares. This means that the better the company's profitability performance, the more positive the market response.…”
Section: Influence Of Profitability As the Moderate Variables On Trading Volumementioning
confidence: 99%